2018
DOI: 10.1002/eji.201747172
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of CD8+ T cell‐mediated suppression of HIV/SIV replication

Abstract: In this article, we summarize the role of CD8 T cells during natural and antiretroviral therapy (ART)-treated HIV and SIV infections, discuss the mechanisms responsible for their suppressive activity, and review the rationale for CD8 T cell-based HIV cure strategies. Evidence suggests that CD8 T cells are involved in the control of virus replication during HIV and SIV infections. During early HIV infection, the cytolytic activity of CD8 T cells is responsible for control of viremia. However, it has been propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 179 publications
(219 reference statements)
2
84
0
Order By: Relevance
“…During acute viral infections, CD8+ T lymphocytes are able to control viral replication by producing cytokines and cytotoxic mediators 3,5 . However, when the infection becomes chronic, a persistent antigen exposure leads to the up-regulation of inhibitory receptors 3,5,12 . Also, at least in certain circumstances, it has been shown that the presence of inhibitory receptors may identify antigen specific chronically stimulated cells 16,17 .…”
Section: Polyfunctional Hiv-1 Specific Response By Cd8+ T Lymphocytesmentioning
confidence: 99%
“…During acute viral infections, CD8+ T lymphocytes are able to control viral replication by producing cytokines and cytotoxic mediators 3,5 . However, when the infection becomes chronic, a persistent antigen exposure leads to the up-regulation of inhibitory receptors 3,5,12 . Also, at least in certain circumstances, it has been shown that the presence of inhibitory receptors may identify antigen specific chronically stimulated cells 16,17 .…”
Section: Polyfunctional Hiv-1 Specific Response By Cd8+ T Lymphocytesmentioning
confidence: 99%
“…Although it is still not clear what controls HIV viral load levels during the prolonged asymptomatic stage, when viral loads are relatively stable over months to years, several immune effector mechanisms are implicated, including innate responses (especially early on), antibody responses, and cellular immune responses . Among these, the most studied, and (perhaps consequently) the one for which there is the most evidence for an effect in controlling HIV, is the cellular immune response mediated by CD8+ T cells …”
Section: Hiv Immune Controlmentioning
confidence: 99%
“…In support of the first explanation, there are many experimental observations that are consistent with a noncytolytic effect of CD8+ T cells. In this context, multiple soluble factors have been found or proposed to reduce viral replication (reviewed in ). Indeed, the possibility of a nonlytic effect was also the conclusion of one of the first studies of chronically SIV‐infected macaques depleted of CD8+ cells described above, where it was found that an effect in viral production was more consistent with the data.…”
Section: Mathematical Modeling Of Cd8+ Cell Depletion Experimentsmentioning
confidence: 99%
“…Additionally, HIV-1-specific CD8 T cells are also important for the control of HIV-1 replication (56). The relevance of the HIV-1-specific CD8 T cell responses has been reinforced by preclinical studies (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%